Meningkatkan Komunikasi Matematika Dengan Strategi Problem Based Learning (PBL) Berbasis Number Head Together (NHT) (Ptk Pada Siswa Kelas VIII SMP Negeri 1 Tulung Tahun Ajaran 2015/ 2016) - Larasati, Dinta Puri; , Dra, N Setyaningsih, M., M.Si; , Sr Rejeki, M.,pd,M,.Sc (2016)
The purpose of this study is to increase the mathematical communication skill through Problem Based Learning strategy based on Number Head Together of students of 8th grade of SMP Negeri 1 Tulung. This is a classroom action research. The subjects in this study were 30 students consisting of 12 male students and 18 female students and the mathematics teachers of 8th grade. The actions were conducted in two cycles consisting of four meetings. The data collection was conducted using observation, test, field notes, and entation. The data were analyzed using data reduction, data presentation, and conclusion. To check the validity of the data the researchers did investigator triangulation. The results showed an increase in the mathematics communication that has been done based on the indicators: 1) the students were able to express mathematical ideas through spoken or written (before action 6.67% after action 56.67%), 2) the students were able to describe the idea into a mathematical model (before action 10% after action 70%), 3) the students were able to write a mathematical idea into visual form (before action 13.33% after action 60%), 4) the students were able to explain the mathematical concept of (before action 10% after action 56.67%). Keywords: mathematical communication, problem based learning, number head together